Aid: dinosaur or development engine for Sub-Saharan Africa? - Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The situation of the 49 countries of sub-Saharan Africa has become even more varied in the past few years. The changes are highly relevant to aid (official development assistance / ODA) and other forms of development financing. The question is what contribution aid can make in the future in an environment undergoing such manifest change. The following structural changes are currently taking place: (1) By and large, sub-Saharan Africa's economic situation has developed positively in the past twenty years, not least because the various countries have pursued better policies. While the majority were characterised in the 1990s by enormous budget deficits, high rates of inflation, government intervention, capital flight and black markets, the countries of the region generally have more room for manoeuvre today, not least with regard to their own budgets. In the last decade a group of some 10 to 20 countries in the region managed to achieve significant growth rates; the international financial and economic crisis did little to alter this. At the same time, there are still a number of countries where economic dynamism is still unsatisfactory or where, despite growth, there has been less than adequate improvement in living conditions. (2) The quality of governance has improved in sub-Saharan Africa as a whole. Public financial management is, on average, better today than it was in the past. Nonetheless, clientelist and neo-patrimonial systems, which have considerable influence on the use of resources, continue to leave their mark in many countries. Reforms aimed at improving the political environment (political openness, etc.) have yet to be undertaken in many countries of the region. (3) International financial flows to sub-Saharan Africa have grown sixfold since 2000. This steep rise has been accompanied by major changes to financial structures, the proportion of private inflows having increased significantly. Aid continues to play an important role, although the scene is increasingly dominated by foreign direct investment and foreign workers' remittances. Such “new cooperation partners” as China, India and Arab countries are also triggering major changes; the importance of South-South relations for sub-Saharan Africa is growing. (4) For oil-exporting countries in particular and for the middle-income countries aid has already become far less important. In the low-income countries and the fragile states, on the other hand, it often continues to play a major role, although even poor countries have stepped up their efforts to become less dependent on it. In fragile countries it frequently plays the role of counteracting state disintegration. Given the dynamic developments in sub-Saharan Africa, it is very important to know precisely what effects internal and external resources have on development processes. A better understanding of relevant internal and external resources and policies will be vital for development research in the coming years.
Keywords: 330